Geographical distribution of 3 allied health professions in South Australia: A summary of access and disadvantage. (12th October 2021) - Yisma, Engida; Gillam, Marianne; Versace, Vincent L.; Jones, Sara; Walsh, Sandra; May, Esther; Jones, Martin
Abstract: Objective: To describe the distribution of 3 allied health professionals—occupational therapists, physiotherapists and podiatrists—in South Australia stratified by the Modified Monash Model and the Index of Relative Socio‐Economic Disadvantage. Design: A descriptive data linkage cross‐sectional study. Setting: The state of South Australia, Australia. Participants and main outcome measures: Distribution of the 3 registered allied health professional groups stratified by Modified Monash Model and Index of Relative Socio‐Economic Disadvantage. Results: The largest proportion of the 3 allied health professional groups (occupational therapists, physiotherapists and podiatrists) were found in areas classified as Modified Monash 1 and Modified Monash 2 (86.5%). The lowest proportion of allied health professionals were found in Modified Monash 7. The largest number of allied health professionals per 10 000 population was found in areas classified as Modified Monash 1 and Modified Monash 2. The lowest number of allied health professionals per 10 000 population was found in Modified Monash 7 areas. The largest number of allied health professionals per 10 000 population was found in areas with Index of Relative Socio‐Economic Disadvantage quintile 2, while the lowest number of allied health professionals per 10 000 population was found in areas with Index of Relative Socio‐Economic Disadvantage quintile 1. Conclusions: The distribution of allied health professionals according to geographical remoteness, socio‐economic disadvantage and per 10 000 population varies widely in South Australia. The number of allied health professionals per 10 000 population was lowest in rural and remote/very remote areas, explaining the typically poor access to allied health services for communities in these areas. The number of allied health professionals per 10 000 population according to Index of Relative Socio‐Economic Disadvantage was variable within the context of both urban and rural areas.